3D visualization of objects using texture based algorithm - Dwivedi, Shriya; Mansi; Malhotra, Lakshay; Dubey, Rashmi (ICRAIE : 2016 International Conference on Recent Advances and Innovations in Engineering : 23-25 December 2016, 2016)
In terms of scientific visualization and computer graphics, volume rendering is actually a set of techniques of procedures that are mainly used to display a two dimensional projection of a three dimensional computed data sets. The function of displaying the volumetric data as a two dimensional image which shows the details to the user. This method is contrasting to the conventional computer graphics in which one has to deal with surfaces. In volume rendering, volume visualization takes structured or unstructured three dimensional data to be rendered into two dimensional image. Various rendering algorithms can be applied for this depending upon the structure and type of data. The basic approach behind our work is to represent the volume of an image into different textures. To make back to front compositing, a number of semi-transparent textured slices are then blended together with an appropriate blending factor. In this paper implementation of a system is done which represents the overall view of any set of 2D images. User can rotate and view each aspect of the data set or image applied. This is very useful in medical, gaming fields and restoration of objects, where can get three dimensional visualization of image data sets. In this paper, can implement the algorithm designed for any bit image and any resolution. The textures enhance the visualization which helps in distinguishing the image parts.